The finality of the gospel: Karl Barth and the tasks of eschatology - Dugan, Kaitlyn; Ziegler, Philip G. (Studies in reformed theology, 2022)
"In this volume, leading systematic theologians and New Testament scholars working today undertake a fresh and constructive interdisciplinary engagement with key eschatological themes in Christian theology in close conversation with the work of Karl Barth. Ranging from close exegetical studies of Barth's treatment of eschatological themes in his commentary on Romans or lectures on 1 Corinthians, to examination of his mature dogmatic discussions of death and evil, this volume offers a fascinating variety of insights into both Barth's theology and its legacy, as well as the eschatological dimensions of the biblical witness and its salience for both the academy and church. Contributors are: John M. G. Barclay, Douglas Campbell, Christophe Chalamet, Kaitlyn Dugan, Nancy J. Duff, Susan Eastman, Beverly Roberts Gaventa, Grant Macaskill, Kenneth Oakes, Christoph Schwöbel Christiane Tietz, Philip G. Ziegler"--